2011
DOI: 10.1111/j.1559-1816.2011.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptible to Social Influence: Risky “Driving” in Response to Peer Pressure1

Abstract: In 2 studies, college students were socially influenced to be risky or not in a driving simulation. In both studies, confederate peers posing as passengers used verbal persuasion to affect driving behavior. In Study 1, participants encouraged to drive riskily had more accidents and drove faster than those encouraged to drive slowly or not encouraged at all. In Study 2, participants were influenced normatively or informationally to drive safely or riskily. As in Study 1, influence to drive riskily increased ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 23 publications
6
59
1
1
Order By: Relevance
“…Despite this caveat, among these 26 studies, we identified that 46% of studies (n = 12) suggest males are more prone to experience deviant peer pressure than females, yet 46% of the studies (n = 12) also found no gender difference in susceptibility to deviant peer pressure. A small minority of studies (n = 2; Nahom et al 2001;Shepherd et al 2011) demonstrated a greater female proneness to be susceptible to peer pressure. Thus, our review of the literature does not appear to support the argument that adolescent females are more susceptible to deviant peer pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this caveat, among these 26 studies, we identified that 46% of studies (n = 12) suggest males are more prone to experience deviant peer pressure than females, yet 46% of the studies (n = 12) also found no gender difference in susceptibility to deviant peer pressure. A small minority of studies (n = 2; Nahom et al 2001;Shepherd et al 2011) demonstrated a greater female proneness to be susceptible to peer pressure. Thus, our review of the literature does not appear to support the argument that adolescent females are more susceptible to deviant peer pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the issue of domain specificity may shed light on another finding in the present review: the small minority of studies (n = 2; Nahom et al 2001;Shepherd et al 2011) that demonstrated a greater female proneness to be susceptible to peer pressure. For example, Nahom et al (2001) relied on a single, domain-specific item: peer pressure to have sexual intercourse.…”
Section: Domain Of Risky Behaviormentioning
confidence: 99%
“…Current literature supports two hypothesized mechanisms: (1) explicit or implicit encouragement of risk taking [9,10] and (2) distraction [11]. These theories have been supported by direct observation studies [9,10], laboratory-based experimental studies [12][13][14], and teen drivers' reports of peer distraction and encouragement of risky driving [11,15,16]. Several of these studies have also reported statistical interactions between passenger and driver gender; specifically, the presence of male passengers leads to riskier driving behaviors, regardless of driver gender, but particularly when traveling with a male driver [9,10].…”
mentioning
confidence: 86%
“…Moreover, Banerjee and Dittmar (2007) argued that consumers often try to avoid losing a sense of belonging in social groups and thus strive to participate in special occasions. Through social influences, the presence of others and their perceptions or preferences can change members' behavior (Sheperd, Lane, Tapscott, & Gentile, 2011); in this case, consumers may feel pressured to dine at restaurants during special occasions. Thus: H6: Subjective norms have a positive effect on consumer intention to dine at restaurants during special occasions.…”
Section: Consumer Attitude Subjective Norms and Behavioral Intentionmentioning
confidence: 98%